Development of a medical education podcast in obstetrics and gynecology - Black, Kristin A; Drummond, Lindsay; Jain, Venu; Sagle, Margaret (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2021)
Implication Statement: Podcasts are used in medical education to supplement conventional teaching methods such as lectures and reading. We identified a lack of Canadian medical education podcasts covering obstetrics and gynecology (Ob/Gyn) content and created a podcast specific for Canadian medical students and residents. The podcast called “OB-G in YEG” is freely available and currently has fourteen episodes that cover common topics in Ob/Gyn. We describe the process for creating a high-quality medical education resource that is widely accessible to learners that readers may be able to replicate in their own discipline.